Implementasi Algoritma Fifo Terhadap Sistem Antrian Pasien di Rumah Sakit Berbasis Web Online - Ismail, Juni; Gea, Muhammad Nasri; Satria, Habib; Tammamah Lubis, Hartati; Prasetya, Hardi; Hanani Hutabarat, Jamina; Sihombing, Rotua; Wanayumini, Wanayumini (Universitas Medan Area, 2024)
The development of queuing systems in hospitals continues to be developed to optimally support patient service, especially regional general hospitals (RSUD). This is because the manual system is still inefficient, resulting in patients queuing for a long time and conflicts often occur. Based on these problems, a Web system was designed with the support of the Fifo algorithm so that the queuing system becomes simpler and more optimal. An easier and more flexible queuing system will support better and more excellent hospital services. Implementation of the Fifo Algorithm, designed to determine and calculate the patient queue system and orderly service for patient registration at the hospital. The implementation of this automatic queuing application will have an impact on health services, especially at Dr. Djasamen Saragih, Pematang Siantar city. The results of using a web-based application in this hospital have an impact in making it easier for operators or admins to queue up calls for patient serial numbers. The operating system on the website is monitored. If the web status has a data result of 1, the patient has been called by admin, but if the patient has not been called, the monitoring site is in Web with value 0 or null.